Análisis de las compras públicas realizadas por una empresa pública como aporte al cumplimiento de sus objetivos: Caso de estudio: Empresa pública Yachay EP durante el periodo 2013 a 2015 - Flor Caravia, María del Amparo (2018)
The present research work analyzes the public purchases made by the public company Yachay EP during the period 2013 to 2015, to define its contribution to the fulfillment of its two primary objectives: administration of the Ciudad del Conocimiento and transformation of the productive matrix. For this purpose, it reviews the regulatory framework, organizational structure - value adding units, and on these bases the interrelationships between the different variables available in public procurement portal information are determined, emphasizing results related to purchases by special regime, hiring for project’s communication social, and finally highlights that, of the processes in the end in analysis, 92.54% of the budget invested in the project corresponds to infrastructure.